Development of SOP (Simulation of Proportion) Learning Media: Simulation Based Sticker Book on Direct and Inverse Proportion - Lathifa Millati Saifullah; Abd Qohar (International Journal of Trends in Mathematics Education Research, 2020)
The objective of this research is to develop a valid, practical, and effective sticker book as learning media on proportion. The name of the learning media is SOP (Simulation of Proportion). This research used research and development approach and ADDIE model which consists of five steps (1) Analyze, (2) Design, (3) Develop, (4) Implement, (5) Evaluate. The subjects of validity test were an expert validator and a practitioner validator. The subjects of pilot study were five 7th grade students out of the subjects of field study. The subjects of field study are 30 students of VII A in SMPN 1 Blitar who have heterogeneous ability. The validation score of SOP attained 3.59, student worksheet attained 3.65, lesson planning attained 3.56, and evaluation test attained 3.61 which implies that they are valid. The score of pilot test attained 3.5 which implies SOP is practical and ready to be applied in the field study. The practical score attained 3.33 implies SOP is practical. Meanwhile, 90% of field study subjects passed the evaluation test with 80 as the criteria of minimum score which implies SOP is effective. Based on the result explained, it can be concluded that SOP (Simulation of Proportion) is valid, practical, and effective such that proper to be applied as learning media for students.